Chemistry of Intermolecular Frustrated Lewis Pairs in Motion: Emerging Perspectives and Prospects. Issue 2 (9th February 2015) - Pu, Maoping; Privalov, Timofei
Abstract This feature article describes the chemistry in motion of frustrated Lewis pairs (FLPs). With state‐of‐the‐art ab initio molecular dynamics (AIMD) simulations supplemented by minimum energy path (MEP) and potential energy surface (PES) calculations, we examine the binding of CO2 and the heterolytic cleavage of H2 by a Lewis base (LB), tBu3P, and a Lewis acid (LA), B(C6F5)3. We strive to uncover and understand mechanistic implications of the physical laws that govern the behavior of a LB and a LA when they react with a third species (e.g., CO2 or H2) at finite temperature. The approximation that we necessarily must make at present is to forgo the quantization of the movement of atoms in favor of the Born‐Oppenheimer molecular dynamics (BOMD), which unfold according to the classical (Newton's) laws of motion. However, strict quantum chemical theory is used to compute all of the forces that govern the dynamics of the macromolecular FLP system. Using physical reasoning and innovative computer simulations, we show that multi‐scale motion is the predominant mechanistic aspect in reactions of the tBu3P/B(C6F5)3 FLP, as well as, conceivably, those of other similar intermolecular FLPs. Insight achieved thus far leads to a novel activity model for intermolecular FLPs and specific predictions, which could be useful for future experimental and theoretical studies of FLP and other chemistries.